The analysis of different perceptions between Avoskin and Wardah skincare consumers - Shafira Putri Bahari; Reny Fitriana Kaban; Hidayat Sofyan Widjaja (Universitas Sultan Ageng Tirtayasa, 2022)
Wardah is one of the halal cosmetic brands that provides products suit to the needs of Indonesian women. According to Top Brand Award data for 2020, most of Wardah's products experienced a decline in buying interest. The decrease in the percentage of interest in buying Wardah skincare products can be caused by the shift of consumers to other brands. Buying interest is how likely a consumer is to buy a brand and service or how likely a consumer is to move from one brand to another, so this study aimed to analyze different perceptions between two skincare consumers, Avoskin and Wardah, using the variables of halal certification, brand ambassador, and beauty vlogger review. The sampling technique used in this study was purposive sampling, taken from the respondents. This study used the Mann-Whitney test as the data analysis method. The result shows that there are significant differences in perceptions of halal certification among Avoskin and Wardah consumers, no significant differences in brand ambassador perceptions among Avoskin and Wardah consumers, and no significant differences in perceptions of beauty vlogger reviews among Avoskin and Wardah consumers.